Lithuanian experience of application the masonry cavity walls in multistory buildings with sound insulation requirements. (October 2019) - Jagniatinskis, Aleksandras; Fiks, Boris; Mickaitis, Marius
Abstract: Cavity walls could be used instead of homogeneous walls in order to reduce the load acting on the ceiling structure while ensuring conformity with the acoustic requirements for buildings. The airborne sound insulation properties of nonbearing cavity walls comprising two masonry leaves with a filled gap are dealt in this paper. Cavity wall structures erected from silicate brickwork, hollow silicate, gypsum, and aerated concrete block work having general surface mass from 125 to 500 kg/m 2 were analyzed under in situ conditions. Standardized calculation methods for the weighted sound reduction index, R w, assessment are compared with the in situ measurement results of apparent, R ′w, index ones. Field measurements of R ′w index were conducted during the mandatory pre-completion testing introduced in Lithuania since 2007 for newly erected buildings. The resonance effect that occurs due to the cavity in the studied structures and reduces R ′ index values below 800 Hz appropriately lessens the single number value, R ′w . By increasing the width of cavity as well as using sound-absorbing material between masonry elements, this limiting frequency may be shifted to the lower frequency band. Obtained measurements data show that standardized models intended for homogeneous walls could properly indicate the sound insulation properties of cavity walls having a relatively high (>350 kg/m 2 ) general surface mass. For cavity walls with lower than 350 kg/m 2 general surface mass values, measurement showed higher R ′w values than for standardized models. The two types of cavity wall supporting are classified for evaluation of the cavity wall together with flanking structures on acting of loads: strong supported and weak supported . For the strong supported structures, increasing of the R ′w index was from 3 dB to 8 dB compared with standardized models. For the weak supported structures, increasing of the R ′w index was from 1 dB to 4 dB for less than 200 kg/m 2 surface mass cavity walls. Appropriate calculation regression formulas were proposed to predict the value of the R ′w index for cavity walls of both types.